Social mobile applications design: case study of social hikers community / Nurul Huda Mohd Razif and Mohamad Razeef Abdul Razak - Mohd Razif, Nurul Huda; Abdul Razak, Mohamad Razeef (Universiti Teknologi MARA, 2020)
The development of technology growth in mobile technologies and applications leads to a challenge and opportunity to a new trend of numerous creative individuals and also the company to create relations with consumers through a portable application. Social mobile application is one of the popular applications and has become essential in human daily life. Sneak Peak social mobile application is a platform for hikers' enthusiasts. Therefore, the purpose of this paper is to identify the limitation of hikers to access information of hiking activities in Malaysia to design social mobile applications for the hiker's community. Moreover, this research aim extensively focuses on hiking recreation experiences, connecting with nature among the Malaysian hikers' community as well as lead to exposure for the social media design elements in executing the outdoors activity for the Malaysian hiker's mobile app. Social mobile application or as a mobile social-activity app, encouraging users to connect with friends and family. A Participatory Design approach was selected to conduct this research and to develop Sneak Peak social mobile application for the hiker's community in Malaysia. This paper provides an explanation and better understanding of the hiking knowledge among hikers and especially beginner hikers to prevent more dangerous problems comes afterwards because of the lack of hiking knowledge through the best medium that is effective in influencing Malaysian Hikers.